Penerapan Payment Gateway pada Aplikasi Wedding Organizer Berbasis Web dengan Metode Agile menggunakan Framework Scrum - Setiawan, Ridwan; Elsen, Rickard; Nur Afifah, Via (Institut Teknologi Garut, 2023)
Wedding Organizer (WO) is an event organization service provider that works directly to assist prospective brides and grooms in planning their wedding event at a predetermined time and cost. Problems that often occur include when clients or prospective brides and grooms decide on wedding packages. The package selection process often takes quite a long time because it requires in-depth discussions. Apart from that, the payment process is also a concern because currently clients can only pay via transfer by sending proof of payment, which takes time to be verified by the admin. The aim of this research is to apply payment gateway technology to a web-based wedding organizer application that can provide information about wedding package services and make orders easily and quickly. The methodology used in this research is Agile with the Scrum Framework through the stages Requirements, Product Backlog, Sprint Planning, Sprint, Sprint Review. and Sprint Retrospective. For system modeling in this research, Unified Modeling Language (UML) is used with 2 diagrams, namely Use Case Diagram and Class Diagram. The result of this research is a web-based wedding organizer application that can make payments in real time by implementing one of the payment gateways, namely Midtrans, making it easier for admins to process payment verification and also so that clients can make transactions easily and quickly.